Earth analogue testing and analysis of Martian duricrust properties. (November 2018) - Lewinger, William; Comin, Francisco; Matthews, Marcus; Saaj, Chakravarthini
Abstract: Previous and current Mars rover missions have noted a nearly ubiquitous presence of duricrusts on the planet surface. Duricrusts are thin, brittle layers of cemented regolith that cover the underlying terrain. In some cases, the duricrust hides safe or relatively safe underneath the top soil. However, as was observed by both Mars exploration rovers, Spirit and Opportunity, such crusts can also hide loose, untrafficable terrain, leading to Spirit becoming permanently incapacitated in 2009. Whilst several reports of the Martian surface have indicated the presence of duricrusts, none have been able to provide details on the physical properties of the material, which may indicate the level of safe traversability of duricrust terrains. This paper presents the findings of testing terrestrially-created duricrusts with simulated Martian soil properties, in order to determine the properties of such duricrusts and to discover what level of hazard that they may represent (e.g. can vehicles traverse the duricrust surface without penetration to lower sub-surface soils?). Combinations of elements that have been observed in the Martian soil were used as the basis for forming the laboratory-created duricrusts. Variations in duricrust thickness, water content, and the iron oxide compound were investigated. As was observed throughout the testing process, duricrusts behave in a rather brittle fashion and are easily destroyed by low surface pressures. This indicates that duricrusts are not safe for traversing and they present a definite hazard for travelling on the Martian landscape when utilising only visual terrain classification, as the surface appearance is not necessarily representative of what may be lying beneath. Highlights: Fabrication of artificial Mars duricrusts based on Mars geology. Empirical testing and evaluation of artificial duricrust mechanical properties. Testing of safe rover trafficability using standard geotechnical site survey methods. Useful for full sensor testing (e.g. Ground Penetrating Radar, soil sampling systems) or as a physical analogue only (e.g. rover sinkage experiments).